Optimization Of Oil Pollution Prevention During Operational Activities Aboard MT. B. STAR - Slamet Prasetyo Sutrisno; Siti Nurlaili Triwahyuni; Fathur Nanda Saputra (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Shipping fleets that are more advanced over time also have a negative impact, just as all types of technological advances cause side effects, including with the increasing number of shipping fleets. After the operation of the ships, it turned out to bring new problems, the phenomenon of Oil Pollution began to appear. So it takes regulations governing the prevention and limitation of matters relating to Oil Pollution. This study aims to analyze the handling of oil Pollution in accordance with the certificate that applies on board MT B Star . The type of research used in this study is qualitative research. In this case the data collection techniques used are interviews and observations. Interviews were in the form of questions and answers with some of the ship's crew who were in place when the Oil Pollution occurred, while observations were in the form of an approach to the object of research. From the results of the research conducted, it can be seen that the handling of Oil Pollution aboard MT B Star is still lacking because of the lack of a sense of responsibility of the crew who does not carry out their duties as stated on the certificate and the number of equipment that is not feasible . These two factors can be lost by the way the crew carries out its duties in accordance with the applicable muster list on board the ship and the shipping company wants to provide decent equipment on board to prevent the occurrence of Oil pollution in this way it can be ensured that the handling of Oil Pollution can be done maximally.